KEANEKARAGAMAN JENIS IKAN AIR TAWAR DI SUNGAI DONG SANDAR DAN SUNGAI REMPANGI DI KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Saputra, Ongki; Anwari, M Sofwan; Herawatiningsih, Ratna (Universitas Tanjungpura, 2019)
Deforestation will affect changes in the condition of the waters of the protected and secondary forest watersheds that can affect in it biota . Fish have limited ability to choose areas that are safe for their lives, especially the environment that is very supportive for the availability of food sources. The fish population in the Dong Sandar River and Rempangi as well as the diversity of fish species in both rivers is unknown. The problem of this research is how the diversity of fish species in the Dong Sandar River and Rempangi River, Sungai Laur District, Ketapang. Research on the diversity of freshwater fish species in the Dong River between the protection of protected forests and the Rempangi River in the secondary forest of Sungai Laur Subdistrict, Ketapang District, West Kalimantan consisting of 20 stations each of which there are 10 observation stations conducted on May 1 - 21, 2018. The selection of observation stations is selected (purposive sampling) which is based on consideration of the conditions and conditions of the aquatic environment. The results of the research were 884 individuals from 50 species of 18 families with the use of scattered, pukat, seluak, bubu, temilar, sauk , and ambe exploration tools. The most types of fish obtained on the Dong Sandar River and Rempangi River consist of the Cyprinidae family (20 species), Bagridae family (7 species), Siluridae family (4 species). The diversity of fish species in the Dong Sandar River and Rempangi River in Ketapang Regency is relatively moderate (H '<3) with a diversity index (H') of 2.94, if H '<1 means low diversity, if 1 <H' <3 means moderate diversity and if H '> 3 means high species diversity. The dominant index (C) on the Dong Sandar River is 0.09 while in the Rempangi River 0.11, the range of dominant index values is 0 - 1 if the value C = 0 means that there are no types of fish dominating and if C = 1 means there are other types of fish dominating. The highest evenness index (E) is found in the Rempangi River of 0.77 and in the Dong Sandar River 0.76, it canÂ be seen the range of evenness of species index 0-1 if the value E = 0 means low type evenness, and if the value E = 1 means evenness is relatively evenly. The species richness index (R) of the Dong Sandar River has abundant types of fish with a value of 7.26 while in the Rempangi River only 4.40. Evenness on both rivers is 57.53%.Keyword :Â Diversity, Dong Sandar River, Fish, Rempangi River